Reconciliation Through Bearing Another's Debt: an Exegetical Study of Philemon 1:17–19 and its Implications for the Contemporary Church - Medi L. Sihombing; Aremi E. Tarigan; Mulina Tarigan; Hanna Pangaribuan; Afriani Manalu (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
This study examines the theological concept of reconciliation through the bearing of another’s debt in Philemon 1:17–19 as a biblical foundation for the ministry of reconciliation in the contemporary church. Although previous studies have explored the historical relationship between Philemon and Onesimus and Paul’s persuasive rhetoric, limited attention has been given to the theological significance of Paul’s willingness to assume Onesimus’ debt as a model of Christian reconciliation. Therefore, this study aims to analyze the exegetical meaning of Philemon 1:17–19 and to explore its implications for the contemporary church. Employing a qualitative method with a New Testament exegetical approach, the study examines the grammatical, syntactical, literary, and theological dimensions of the text. The findings reveal that reconciliation in this passage extends beyond interpersonal conflict resolution to the restoration of relationships grounded in shared identity in Christ. Paul’s willingness to bear Onesimus’ debt represents substitutive solidarity that reflects the redemptive pattern of Christ’s sacrificial work and demonstrates that genuine reconciliation requires personal responsibility, sacrificial love, and active participation in restoring broken relationships. The study concludes that Philemon 1:17–19 offers a robust theological framework for reconciliation that is both spiritually transformative and socially restorative, providing a relevant paradigm for the contemporary church in addressing relational conflicts and fostering authentic Christian community.